2014
DOI: 10.1523/jneurosci.0548-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Decoding in Human Visual Cortex: New Insights from an Unbiased Perspective

Abstract: The development of multivariate pattern analysis or brain "decoding" methods has substantially altered the field of fMRI research. Although these methods are highly sensitive to whether or not decodable information exists, the information they discover and make use of for decoding is often concealed within complex patterns of activation. This opacity of interpretation is embodied in influential studies showing that the orientation of visual gratings can be decoded from brain activity in human visual cortex wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 27 publications
1
76
3
Order By: Relevance
“…It has been suggested that decoding performance could be due to coarse-scale effects such as radial biases (Mannion et al, 2010), edge effects (Carlson, 2014), or differential allocation of attention . Some of these possibilities for orientation decoding using MEG have been ruled out by careful control experiments (Cichy et al, 2015), but might there be similar confounds for decoding eye-of-origin?…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that decoding performance could be due to coarse-scale effects such as radial biases (Mannion et al, 2010), edge effects (Carlson, 2014), or differential allocation of attention . Some of these possibilities for orientation decoding using MEG have been ruled out by careful control experiments (Cichy et al, 2015), but might there be similar confounds for decoding eye-of-origin?…”
Section: Discussionmentioning
confidence: 99%
“…Here, we elaborate the mathematical relationship between spirals of opposite sense to confirm that they cannot be discriminated on the basis of the pooled output of unbiased or radially biased orientation filters. We then demonstrate that Carlson's (2014) reported decoding ability is consistent with the presence of inadvertent biases in the set of orientation filters; biases introduced by their digital implementation and unrelated to the brain's processing of orientation. These analyses demonstrate that spirals must be processed with an orientation bias other than the radial bias for successful decoding of spiral sense.…”
mentioning
confidence: 65%
“…Despite this, Carlson (2014) has recently claimed that spirals of opposite sense can be discriminated from a representation of local image structure that is unbiased with respect to orientation. On this basis, it was argued that "there is no need to posit a bias either at fine grain or coarse-scale representation to account for decoding spiral sense" (Carlson, 2014).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…In multivoxel pattern analysis (right), machine learning techniques are used to train a classifier to distinguish categories based on fine-grained activation patterns (yellow box) and its classification performance is evaluated on a separate test set (red box). from visual cortex because imperfect sampling of orientation-selective columns leads to hyperacuity (Kamitani & Tong, 2005), because of radial biases in the retinotopic map (Freeman et al, 2011), or because of edge-related activity (Carlson, 2014). Ritchie et al (2017) further suggest that relating classifier performance to behavior only partly remedies the problem as "a brain region might carry information which is reliably correlated with the information that is actually used, but which is not itself used in behavior".…”
Section: Univariate Vs Multivariate Analysismentioning
confidence: 99%